Linguistic Correction in Transitive and Intransitive Verbs According to Muhammad al-Adnani: An Evaluative Study - آوختي, ماجد حميد; آغا, طه صالح أمين (Sulaimani Journal for Humanities, 2020)
This research is an evaluation study of the reality of linguistic correction in the Transitive and Intransitive verbs of Muhammad Al-Adnani, through his two glossaries of common mistakes and contemporary linguistic mistakes. The truth is that these two dictionaries testify to their owners along the vendors in the field of linguistic correction, by displaying many linguistic materials on the scale of misrepresentation and correction, followed by often brief evidence that indicates the mistake and its correctness. But this does not prevent those whose efforts in correction and misinformation of linguistic materials are surrounded by research and study, from our desire to reveal their merits of study and reasoning, and to evaluate what may be reminiscent of human memory, a true aspect of Arabic, and to warn about what Adnani has missed from the inference of the wrong in the language. The nature of the topic required the research to be based on two requirements, we talked briefly on the first demand about (Al-Adnani's biography and his approach to linguistic correction), while the second demand focused on talking about his linguistic corrections in the Transitive and Intransitive verbs.